PENGARUH CAPITAL STRUCTURE, PROFITABILITY, FIRM SIZE, DAN LEVERAGE TERHADAP FIRM VALUE - Sri Yulia Agustina, Thio Lie Sha (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence of the effect of Capital Structure, Profitability, Firm Size, and Leverage to Firm Value on manufacturing company listed in Indonesia Stock Exchange (IDX)on period 2015-2017. This research used 66 manufacturing company as the sample with purposive sampling method. Application that is used in this research is Eviews 9.Based on F-test states that every independent variables in this research have a significant effect to Firm Value. Based on t-tests, the results are Capital Structure have a negatif and significant effect to Firm Value. Whereas Profitability and Leverage  have a positive and significant effect to Firm Value. And Firm Size has a positive and insignificant  effect to Firm Value.